Investor adoption of robo-advisors and its determinants in Malaysia - Cheah, Wai Kent (2022)
Despite the tremendous growth of financial robo-advisor recorded in 2020, financial robo-advisor market in Malaysia is significantly smaller than the traditional asset management industry whereby its assets under management (AUM) is less than 0.1 percent of the AUM of traditional asset management industry. This research attempts to examine and understand the determinants of financial robo-advisor usage over traditional asset manager in Malaysia. After considering and comparing the various models relating to the adoption of technology, Technology Acceptance Model (TAM) was selected for this research as it is the most parsimonious, yet flexible model to accommodate the objectives of this research. The proposed research model was developed based on the relationship formulated in the original TAM and was extended by including subjective norms as additional variable and familiarity with traditional asset managers as moderating variable. Quantitative approach was adopted, and survey questionnaire was developed and disseminated online. A total of 209 responses were collected and 204 responses were eligible and usable in this research. Partial least squares structural equation modeling (PLS-SEM) technique was employed to analyze the research data in SmartPLS 3.0 statistical software. Data normality was examined and the results showed that all items are within the skewness and kurtosis thresholds. The assessment of measurement model also confirmed the reliability and validity of the indicators and constructs. The hypotheses test revealed that all relationships are significant, except for the hypotheses that involved moderating effect. The research concluded that perceived ease of use, perceived usefulness, attitude and subjective norms are the determinants of investors on the usage intention of financial robo-advisors in Malaysia.